Адаптивний оптичний сенсор на планарному хвилеводі для системи екологічного моніторингу - Галат, О. Б.; Стаднік, Д. В.; Лашко, Е. І. (ХНУРЕ, 2025)
This paper investigates an adaptive optical sensor based on a planar waveguide for environmental monitoring systems. The proposed design offers a simpler technological alternative to D-shaped fiber sensor while retaining the advantages of total internal reflection and evanescent-field interaction. The study includes modeling of light propagation in the glass plate and calculation of key parameters such as penetration depth, number of reflections, and total attenuation. The results show that adjusting the input angle provides an effective mechanism for tuning sensor sensitivity. The approach enables the development of a flexible, microcontroller-controlled multispectral system suitable for field environmental measurements.
Keywords: оптичний сенсор; планарний хвилевід; екологічний моніторинг